Value consciousness and purchase intention: Mediation by information seeking in Social Networking Sites - S. , Aswini priya; Venugopal, Pulidindi (International Journal of Psychosocial Rehabilitation, 2020)
Companies have started to integrate digital marketing into their marketing mix to reach a large audience. The social e-shopping is also augmenting, and consumers’ intentions to purchase through SNS are also increasing. The communities in social e-shopping are augmenting in terms of size and number where the users share about the product information and its performance. Hence the study determines the impact of value consciousness on information seeking in SNS and eventually intention to purchase using SNS. The study also determines the mediating effect of information seeking in SNS on the relationship between value consciousness and intention to purchase using SNS. The questionnaire was administered in online mode, and a valid sample of 380 responses was taken back for further analysis. The research used statistical tools such as regression analysis and process macro to fulfil the purpose of the study. The results showed that those consumers who are value conscious tend to seek information in SNSs and also hold a positive intention to purchase through SNSs. It is also clear from the result that information seeking in SNS mediates the relationship between value consciousness and purchase intention among SNS users.